Engineering Nicotiana tabacum trichomes for triterpenic acid production. (March 2023) - Gossart, Nicola; Berhin, Alice; Sergeant, Kjell; Alam, Iftekhar; André, Christelle; Hausman, Jean-François; Boutry, Marc; Hachez, Charles
Abstract: In this work, we aimed at implementing the biosynthesis of triterpenic acids in Nicotiana tabacum glandular trichomes. Although endogenous genes coding for enzymes involved in such biosynthetic pathway are found in the Nicotiana tabacum genome, implementing such pathway specifically in glandular trichomes required to boost endogenous enzymatic activities. Five transgenes coding for a farnesyl-diphosphate synthase, a squalene synthase, a squalene epoxidase, a beta-amyrin synthase and a beta-amyrin 28-monooxygenase were introduced in N.tabacum, their expression being driven by pMALD1, a trichome-specific transcriptional promoter. This study aimed at testing whether sinking isoprenoid precursors localized in plastids, by exploiting potential cross-talks allowing the exchange of terpenoid pools from the chloroplast to the cytosol, could be a way to improve overall yield. By analyzing metabolites extracted from entire leaves, a low amount of ursolic acid was detected in plants expressing the five transgenes. Our study shows that the terpene biosynthetic pathway could be, in part, redirected in N.tabacum glandular trichomes with no deleterious phenotype at the whole plant level (chlorosis, dwarfism, …). In light of our results, possible ways to improve the final yield are discussed. Highlights: Triterpene biosynthesis can be implemented in tobacco trichome secretory cells Terpene biosynthesis can be redirected to produce triterpenic acid in glandular trichomes. Further research is needed to overcome yield limiting steps